2022
DOI: 10.1073/pnas.2120617119
|View full text |Cite
|
Sign up to set email alerts
|

Loss of glucose 6-phosphate dehydrogenase function increases oxidative stress and glutaminolysis in metastasizing melanoma cells

Abstract: Significance Melanoma metastasis is limited by oxidative stress. Cells that enter the blood experience high levels of reactive oxygen species and usually die of ferroptosis. We found that melanoma cells become more dependent upon the oxidative pentose phosphate pathway to manage oxidative stress during metastasis. When pentose phosphate pathway function was impaired by reduced glucose 6-phosphate dehydrogenase ( G6PD ) function, melanoma cells increased malic enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Combined, these data suggest that the major metabolic features distinguishing the LAMP2A-KO from WT tumors are the PPP and mitochondrial metabolism, both required to support a high proliferation rate. Further, consistent with the findings that metastasizing melanoma cells depend on G6PD 26 , our findings signify that LAMP2A deficient cancer cells undergo a metabolic switch to become more reliant on G6PD and PPP function.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Combined, these data suggest that the major metabolic features distinguishing the LAMP2A-KO from WT tumors are the PPP and mitochondrial metabolism, both required to support a high proliferation rate. Further, consistent with the findings that metastasizing melanoma cells depend on G6PD 26 , our findings signify that LAMP2A deficient cancer cells undergo a metabolic switch to become more reliant on G6PD and PPP function.…”
Section: Resultssupporting
confidence: 90%
“…Further, consistent with the findings that metastasizing melanoma cells depend on G6PD 26 , our findings signify that LAMP2A deficient cancer cells undergo a metabolic switch to become more reliant on G6PD and PPP function.…”
Section: Cma Deficiency Rewires the Tumor Metabolomesupporting
confidence: 90%
“…One explanation for this is the paradoxical finding by Zhao et al that in A549 cells, the constitutive activation of NRF2 results in both high expression of oxidative PPP enzymes and reduced dependence on the oxidative PPP for cell growth [15]. Another study in melanoma cells, which also have high PPP activity, found that when G6PD function was impaired, there was no reduction in erythrose-4-phosphate levels [26]. These studies demonstrate that cancer cells are resilient to G6PD inhibition and may continue to fuel the non-oxidative PPP through alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of 6-An thus should be considered when it is used to inhibit G6PD enzyme activity. 6-An does not affect G6PD, but instead, blocks 6PGD( Aurora et al, 2022 ). Earlier in vivo studies revealed that 6-An inhibits the carbon-atom transfer from glucose to ribose and suppresses oxPPP ( Köhler et al, 1970 ).…”
Section: Inhibitorsmentioning
confidence: 97%